Effect of Oil Pulling with Sesame Oil on Plaque-induced Gingivitis: A Microbiological Study - Saravanan, Deepshika; Ramkumar, Shubashini; Vineetha, K (Journal of Orofacial Research, 2013)
Oil pulling’ or ‘oil swishing’ is a traditional Indian folk remedy that has both dental and systemic effects. This study has been conducted to evaluate the effect of oil pulling with sesame oil on plaque, gingivitis and colony forming bacteria. For this study we selected 40 subjects with mild to moderate plaque and gingivitis. 20 of them performed oil pulling for 45 days, using sesame oil and the rest 20 continued with their normal oral hygiene measures. Their plaque and gingival scores and colony forming unit counts were assessed before and after oil pulling. Oil pulling resulted in a statistically significant decrease in plaque, gingival scores and number of bacteria in the mouth. This paper explains about the dental benefits of oil pulling on plaque, gingivitis and mouth residing bacteria.